Deciding Death - Lain, Corinna Barrett (2007)
When the Supreme Court is deciding death, how much does law matter? Scholars long have lamented the majoritarian nature of the Court's Eighth Amendment '' evolving standards of decency '' doctrine, but their criticism misses the mark. Majoritarian doctrine does not drive the Court's decisions in this area; majoritarian forces elsewhere do. To make my point, I first examine three sets of '' evolving standards '' death penalty decisions in which the Court implicitly or explicitly reversed itself, attacking the legal justification for the Court's change of position and offering an extralegal explanation for why those cases came out the way they did. I then use political science models of Supreme Court decisionmaking to explain how broader social and political forces push the Court toward majoritarian death penalty rulings for reasons wholly independent of majoritarian death penalty doctrine. Finally, I bring the analysis full circle, showing how broader sociopolitical forces even led to the development of the '' evolving standards '' doctrine. In the realm of death penalty decisionmaking, problematic doctrine is not to blame for majoritarian influences; rather, majoritarian influences are to blame for problematic doctrine. The real obstacle to countermajoritarian decisionmaking is not doctrine, but the inherently majoritarian tendencies of the Supreme Court itself